IMPROVING STUDENTS’ MOTIVATION ON LEARNING ENGLISH THROUGH STUDENT TEAMS-ACHIEVEMENT DIVISIONS METHOD - despita kurniawan (Journal of English Education, Literature and Linguistics, 2021)
The objectives of the research were to identify and to what extent STAD method can improve students’ learning English motivation, and to describe strength and weakness of implementing STAD in this research. This research is a classroom action research. In collecting the data, the researcher used questionnaire, observation, interview and tests. The researcher conducted the tests and questionnaires before research (pre-test) and after implementing the method (post-test 1 and 2). The mean score of each test and questionnaire were compared to know the students improvements in motivation and reading skill. The research finding showed that the motivation of students improved in every cycle. The improvement of students’ motivation can be seen from the improvement of mean score of questionnaire (60. 72) before action, in cycle 1 62.03, and cycle 2 63.03. Besides, the reading skill of the students also improved. The improvement can be seen from the improvement of mean score of pre-test (59.75), post test of cycle 1 69.25, and post test of cycle 2 74.38. The researcher also found strength and weakness of this method.